Association between night pain and quality of life in women: A general population sleep study. (25th December 2022) - Lucena, Leandro; Lavigne, Gilles; Fabbro, Cibele Dal; Andersen, Monica Levy; Tufik, Sergio; Hachul, Helena
Abstract: Background: Women with pain present decreased sleep duration and quality of life, but little is known about the consequences of nighttime pain on overall health. Our goal was to compare levels of anxiety, depression and fatigue in women with pain during the night with those without pain. We hypothesized that pain perception is associated with the worsening of fatigue and mood. Methods: In total, 244 women aged 20–80 years who took part in the Epidemiologic Sleep Study (EPISONO) met the inclusion criteria, 85 in the self‐reported pain group and 171 in the control group. Participants were assigned to the pain group if they both responded (i) they generally had pain, according to Pre‐Sleep Questionnaire (PSQ) and (ii) their pain generally interfered with their sleep 3 or more times a week, according to Pittsburg Sleep Quality Index (PSQI). Those who answered negatively to both questions were allocated to the control group. All participants underwent a full night laboratory polysomnography, and completed questionnaires related to fatigue, depression, anxiety and quality of life. Results: Pain group participants had a significantly lower perception of quality of life, and significantly higher levels of fatigue (5.4 times), anxiety and depression. Pain perception was also correlated to levels of anxiety and depression in the psychological (rs = −0.463, −0.607, respectively) and social (rs = −0.423, −0.438, respectively) quality of life domains. Conclusions: Nighttime pain in women was associated with decreased quality of life, worsening mood and fatigue. Our data shows the importance of investigating pain and its deleterious effects on women's health. Significance: Our study highlights that women experiencing nighttime pain also reported worse mood outcomes and decreased quality of life, regardless of the level and type of pain. Our data, based on association analysis and not investigating causality, suggest it is important to consider nighttime pain in clinical care to improve quality of life and general health.